The Potential of Plant Growth-Promoting Fungi Enhances the Growth, Yield, and Phytochemical Compounds of Oryza sativa L. (Maled Phai Cultivar) Under Field Conditions - Seemakram, Wasan; Nacoon, Sabaiporn; Ekprasert, Jindarat; Theerakulpisut, Piyada; Sanitchon, Jirawat; Boonlue, Sophon (Plants (Basel), 2025)
Excessive application of a chemical fertilizer during rice cultivation leads to soil infertility and increases production costs. An alternative way to reduce over-fertilization is to partially or fully replace the fertilizer with microbes that promote the growth and production of plants. This study aimed to investigate the Maled Phai rice cultivar (Oryza sativa L.) in a field experiment with two fungi strains. Rhizophagus variabilis KS-02 and Trichoderma zelobreve PBMP16 were selected as inocula and compared with non-R. variabilis KS-02 and non-T. zelobreve PBMP16, acting as controls, one without synthetic fertilizer and one with synthetic NPK fertilizer. The field experiment was conducted in a Randomized Complete Block design with four replications. Growth and yield parameters were determined in the plant tissues and roots, and bioactive compounds were determined in the rice seeds. The results show the presence of T. zelobreve PBMP16 and R. variabilis KS-02 colonization in the plant roots at the harvest stage. A single inoculum of both R. variabilis KS-02 and T. zelobreve PBMP16 significantly increased most of the plant growth performance and yield parameters, as well as the concentrations of bioactive compounds. Remarkably, such effects were more apparent than those observed with the use of a chemical fertilizer. Thus, a single inoculum of R. variabilis KS-02 or T. zelobreve PBMP16 and the co-inoculation of both have the potential to increase the grain yield and bioactive compounds of Maled Phai under field conditions.